Advancing Equitable Ambulatory Telehealth Through Dashboard Development - Leah R. Meisel; James P. Marcin; Zhong Wu; Kathryn M. Lopez; Mark Avdalovic; Jennifer L. Rosenthal (Telemedicine Reports)
Telehealth has the potential to improve access to health care by mitigating barriers related to geography, time, and finances. However, the increased adoption of ambulatory telehealth has inadvertently widened access gaps for socially disadvantaged and marginalized populations. Quality improvement approaches are a valuable strategy to address health care access inequities and disparities, involving data-driven implementation, assessment, and adaptation of tests of change over time. Because these iterative changes and interventions are data-driven, a critical element of quality improvement requires ongoing data collection and monitoring. This perspective describes the development and validation processes of a telehealth equity dashboard. This dashboard is currently available for use by our health system leaders, providers, and clinic staff. The overall objective of this dashboard is to identify and track inequities and to improve equitable ambulatory telehealth access across diverse patient groups. Lessons learned from creating this dashboard can inform other health care systems of how to develop and validate telehealth data feedback systems to promote quality improvement efforts to advance telehealth equity and accessibility.